Improvement of bottled coconut jam - Llido, Ma. Jesusa B.; Quintos, Sarah V. (1994.)
The research was conducted to improve the formulation and process of bottled coconut jam. First, a product profile of cocojam was developed using the QDA method. The product profile was then compared to the product profile of cocojam produced using the process and formulation developed by ITDI. A t-test for difference showed the 'variable' product was light brown in color, less sticky, had a weaker caramel taste and very weak burnt taste. Cocojam was improved through the addition of pineapple flavor and tidbits. This product was compared to plain cocojam. Results of sensory evaluation showed that the pineapple cocojam had identical color as plain cocojam, thicker consistency, moderate coco-pineapple flavor and odor, and higher acceptability scores. Lastly, the process and formulation of pineapple cocojam was standardized at bench-scale production. Product costing was done and results showed a 250 g bottle costs about P14.71. Physico-chemical tests such a water activity, % soluble solids, pH, % ash, and viscosity measurements were likewise done. Results showed pineapple cocojam had a water activity level of 0.73-0.80. a % soluble solids content of 68-72%, pH 4.1-4.2, % ash of 0.61-0.70 and a viscosity of 215,000-230,000 centipoise.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Coconut jam